Gene-Editing Technologies Paired With Viral Vectors for Translational Research Into Neurodegenerative Diseases - Rittiner, Joseph Edward; Moncalvo, Malik; Chiba-Falek, Ornit; Kantor, Boris (Frontiers in Molecular Neuroscience, 2020)
Diseases of the central nervous system (CNS) have historically been among the most difficult to treat using conventional pharmacological approaches. This is due to a confluence of factors, including the limited regenerative capacity and overall complexity of the brain, problems associated with repeated drug administration, and difficulties delivering drugs across the blood-brain barrier (BBB). Viral-mediated gene transfer represents an attractive alternative for delivery of therapeutic cargo to the nervous system. Crucially, it usually requires only a single injection, whether that be a gene replacement strategy for an inherited disorder or the delivery of a genome- or epigenome-modifying construct for treatment of CNS diseases and disorders. It is thus understandable that considerable effort has been put towards the development of improved vector systems for gene-transfer into the CNS. Different viral vectors are of course tailored to their specific applications, but they generally should share several key properties. The ideal viral vector incorporates a high-packaging capacity, efficient gene transfer paired with robust and sustained expression, lack of oncogenicity, toxicity and pathogenicity, and scalable manufacturing for clinical applications. In this review, we will devote attention to viral vectors derived from human immunodeficiency virus type 1 (lentiviral vectors; LVs) and adeno-associated virus (AAVs). The high interest in these viral delivery systems vectors is due to (i) robust delivery and long-lasting expression, (ii) efficient transduction into postmitotic cells, including the brain, (iii) low immunogenicity and toxicity, and (iv) compatibility with advanced manufacturing techniques. Here, we will outline basic aspects of LV and AAV biology, particularly focusing on approaches and techniques aiming to enhance viral safety. We will also allocate a significant portion of this review to the development and use of LVs and AAVs for delivery into the CNS, with a focus on genome and epigenome-editing tools based on CRISPR/Cas9 and the development of novel strategies for treatment of NDDs.